HOW TO DEVELOP STUDENTS’ SELF-EFFICACY? DESCRIPTION AND EVALUATION OF A LEARNING EXPERIENCE IN THE TRANSLATION CLASSROOM - Haro Soler, María del Mar (2017)
This paper aims at filling the gap regarding the need to incorporate self-efficacy in translator training programmes in a structured way (Atkinson & Crezee, 2014). It describes a learning experience implemented in the translation classroom aimed at developing students’ translation self-efficacy, i.e., their confidence in their abilities to translate (Bandura 1987, 1997; Haro-Soler, 2017a, 2017b). This experience included practices such as goal-setting as a motivational incentive, verbal persuasion, vicarious learning, and activities to promote students’ self-awareness. The results of an empirical-descriptive study performed to qualitatively and quantitatively assess this training experience from the participants’ perspective will also be presented. The results were obtained from an online questionnaire that all 15 participants were asked to complete and showed that, in their opinion, the learning experience implemented was useful for their training as translators. Participants also suggested that initiatives intended to help students trust their abilities should be incorporated not only into translator training but in higher education programs in general.